Clinical Performance of Glass Ionomer in Class V Restorations: One-Year Follow-Up of Pilot Study - Muhammad Syafiq Alauddin; Normaliza Ab Malik; Norazlina Mohammad (Universiti Sains Islam Malaysia, 2024)
This study's purpose is to evaluate the clinical performance of Class V restorations in non-carious cervical lesions (NCCL's) using conventional glass ionomer Riva Self Cure (SDI) materials in a teaching institute for one-year follow-up. Participants with Class V restorations were recruited from the e-clinical database and reviewed after one-year. Two independent calibrated examiners were assigned to the clinical assessment with high inter-examiner reliability (? =0.82). Modified Ryge / USPHS criteria was used for direct evaluation of the clinical performance of restorations. The criteria assessed were anatomical form, the presence of secondary caries, retention, marginal adaptation, surface staining, soft tissue health and post-operative sensitivity. Class V restoration restored with glass ionomer showed 80.9% retention rate. Secondary caries, retention, surface staining and soft tissue health showed high scoring of A (clinically excellent restoration) (>90%). The highest acceptable restoration percentage (A- clinically excellent restoration + B-clinically acceptable) was surface staining while the lowest scoring categories was post-operative sensitivity. There was significant difference between gender and post-operative sensitivity (p<0.05). Spearman Correlation test showed that the gender was significantly correlated with post-operative sensitivity (r=0.48) while marginal adaptation was significantly associated with anatomical form (r=0.36) and secondary caries (r=0.39). In summary, after one-year follow, conventional glass ionomers are still clinically acceptable material to restore Class V and come with minimal complications. Clinical Significance: Class V restorations restored with conventional glass ionomer is still relevant as a material of choice to restore NCCL's despite the advancement of resin based materials.